Endogenous competition alters the structure of optimal auctions - Ronald M. Harstad (Osaka University, Institute of Social and Economic Research (ISER), 2011)
Potential bidders respond to a seller's choice of auction mechanism for a common-value or affiliated-values asset by endogenous decisions whether to incur an information-acquisition cost (and observe a private estimate), or forgo competing. Privately informed participants decide whether to incur a bid-preparation cost and pay an entry fee, or cease competing. Auction rules and information flows are quite general; participation decisions may be simultaneous or sequential. The resulting revenue identity for any auction mechanism implies that optimal auctions are allocatively efficient; a nontrivial reserve price is revenue-inferior. Optimal auctions are otherwise contentless: any auction that sells without reserve becomes optimal by adjusting any one of the continuous, spanning parameters, e.g., the entry fee. Seller's surplus-extracting tools are now substitutes, not complements. Many econometric studies of auction markets are seen to be flawed in their identification of the number of bidders.
Keywords: D44; D82; C72; 330; optimal auctions; endegenous bidder participation; affiliated-values; common-value auctions; surplus-extracting devices; Auktionstheorie; Asymmetrische Information; Nichtkooperatives Spiel; Theorie